Driving Performance Through Agile Leadership and Motivation: The Mediating Role of Organizational Citizenship Behavior - Dewanti, Amalia Suci; Nurhayati, Mafizatun (Asean International Journal of Business, 2025)
Purpose – This study aims to examine the influence of Agile Leadership and Intrinsic Motivation on Employee Performance, with Organizational Citizenship Behavior (OCB) as a mediating variable at the Education Quality Assurance Agency (BPMP) of North Maluku Province, Indonesia. Methodology/approach – A quantitative survey method was employed, collecting data from 60 respondents using validated questionnaires. The data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). Findings – The results indicate that Agile Leadership and Intrinsic Motivation have a significant positive effect on both OCB and Employee Performance. Furthermore, OCB significantly mediates the relationship between Agile Leadership, Intrinsic Motivation, and Employee Performance. Novelty/value –  This study contributes to the literature by integrating Agile Leadership, Intrinsic Motivation, and OCB in a public sector context. It emphasizes the role of adaptive leadership and intrinsic drive in enhancing discretionary work behaviors and improving performance in bureaucratic institutions.